The impact of Everything But Arms on EU relative labour demand - Ronald B. Davies; Rodolphe Desbordes (University College Dublin, UCD School of Economics, 2016)
The Everything But Arms agreement, introduced by the EU in 2001, eliminated duties on most imports from the least developed countries. To avail of these benefits, however, the exported product must contain a sufficiently large share of local content. Thus, the agreement may have affected both the quantity and the factor content of exports from the least developed countries to the EU. Using a panel of sector-level data across countries, our estimates suggest that, contrary to expectations, the agreement may have increased the skill-content of these exports, benefitting the lowest-skilled EU workers at the expense of their highest-skilled counterparts. This result, however, is entirely driven by textile trade; when omitting this industry, we find no significant effects. This suggests that the EBA may have led to the local provision of higher-skill inputs in the textile industry.
Keywords: F16; F13; 330; Everything But Arms; Local Content; Trade Agreements; Relative Wages